'Cruel optimism': teacher attachment to professionalism in an era of performativity. Issue 5 (2nd September 2016) - Moore, Alex; Clarke, Matthew
Abstract: This study provides a critical exploration of the way teachers' attachment to notions of professionalism may facilitate a process whereby teachers find themselves obliged to enact centralised and local education policies that they do not believe in but are required to implement. The study argues that professionalism involves an entanglement of (past) occupational and (present) organisational discourses and that the remainders of the former facilitate the enactment of the latter. The study draws on Berlant's notion of cruel optimism to help understand this process, whereby teachers' attachment to professionalism may assist them in undermining the very values they believe it embodies.